أحكام نشوز الزوجة في ضوء الفقه الإسلامي والقانون الأفغاني وتطبيقاتها المعاصرة في أفغانستان = The ruling on wife’s disobedience (nushuz) in light of Islamic jurisprudence and Afghan law and its contemporary applications in Afghanistan - Hakimi, Mohammad Naeem; Elshobake, Mohammed R. M.; Jaapar, Ghazali (AL HIKMAH RESEARCH & PUBLICATION CENTRE, 2025)
يتناول هذا البحث أحكام نشوز الزوجة في الفقه الإسلامي والقانون الأفغاني وتطبيقاته المعاصرة، حيث تكمن مشكلة البحث في التباين بين الأحكام الشرعية والتطبيقات القانونية والعرفية. ويهدف هذا البحث إلى توضيح مفهوم النشوز، وبيان أحكامه، وتحليل موقف القانون الأفغاني منه، واستعراض تطبيقاته المعاصرة. ويعتمد هذا البحث على المنهج الاستقرائي والتحليلي والمقارن لاستقراء النصوص الشرعية وتحليها قانونيًا. ويخلص هذا البحث إلى أن الفقه الإسلامي وضع مراحل متعددة لمعالجة النشوز، في حين أن القانون الأفغاني يتأثر بالفقه الحنفي والعرف القبلي. ويوصي هذا البحث بمراجعة الأحكام الشرعية والقوانين الأفغانية، والعمل على نشر الوعي الأسري = This research examines the rulings on a wife’s disobedience (nushuz) in Islamic jurisprudence and Afghan law, and its contemporary application. The research problem the discrepancy between Islamic legal provisions and their legal and customary implementations. The study aims to clarify the concept of nushuz, outline its rulings, analyze the stance of Afghan law on the issue, and review its modern applications. This research employs inductive, analytical, and comparative methodologies to examine and interpret Islamic legal texts form a legal perspective. The study concludes that Islamic jurisprudence established multiple stages for addressing nushuz, whereas Afghan law is influenced by Hanafi jurisprudence and tribal customs. The research recommends a review of both Islamic rulings and Afghan laws, as well as efforts to raise awareness of family issues.